Discrimination of Tumorous Intracerebral Hemorrhage from Benign Causes Using CT Densitometry - Choi, Y.S.; Rim, T.H.; Ahn, S.S.; Lee, S.-K. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: Differentiation of tumorous intracerebral hemorrhage from benign etiology is critical in initial treatment plan and prognosis. Our aim was to investigate the diagnostic value of CT densitometry to discriminate tumorous and nontumorous causes of acute intracerebral hemorrhage. MATERIALS AND METHODS: This retrospective study included 110 patients with acute intracerebral hemorrhage classified into 5 groups: primary intracerebral hemorrhage without (group 1) or with antithrombotics (group 2) and secondary intracerebral hemorrhage with vascular malformation (group 3), brain metastases (group 4), or primary brain tumors (group 5). The 5 groups were dichotomized into tumorous (groups 4 and 5) and nontumorous intracerebral hemorrhage (groups 1–3). Histogram parameters of hematoma attenuation on nonenhanced CT were compared among the groups and between tumorous and nontumorous intracerebral hemorrhages. With receiver operating characteristic analysis, optimal cutoffs and area under the curve were calculated for discriminating tumorous and nontumorous intracerebral hemorrhages. RESULTS: Histogram analysis of acute intracerebral hemorrhage attenuation showed that group 1 had higher mean, 5th, 25th, 50th, and 75th percentile values than groups 4 and 5 and higher minimum and 5th percentile values than group 2. Group 3 had higher 5th percentile values than groups 4 and 5. After dichotomization, all histogram parameters except maximum and kurtosis were different between tumorous and nontumorous intracerebral hemorrhages, with tumors having lower cumulative histogram parameters and positive skewness. In receiver operating characteristic analysis, 5th and 25th percentile values showed the highest diagnostic performance for discriminating tumorous and nontumorous intracerebral hemorrhages, with 0.81 area under the curve, cutoffs of 34 HU and 44 HU, sensitivities of 65.6% and 70.0%, and specificities of 85.0% and 80.0%, respectively. CONCLUSIONS: CT densitometry of intracerebral hemorrhage on nonenhanced CT might be useful for discriminating tumorous and nontumorous causes of acute intracerebral hemorrhage. ICHintracerebral hemorrhageNECTnonenhanced CT